Investigation on surface modified Al7075 with niobium by friction stir processing. (2021) - Makeshkumar, M.; Surender, S.R.; Madesh, R.; Sasi Kumar, M.; Shankar, K.P.
Abstract: In this present work Aluminum alloy 7075 is used as a base metal and niobium is used as an additive material to enhance the surface microstructure and mechanical properties like tensile strength, hardness and wear by using friction stir processing method. For optimizing the process parameters Taguchi L9 orthogonal array has been used. The process parameters for the present work are rotational speed, transverse speed and groove width. The experimental results indicate that rotational speed of 900 rpm, transverse speed of 20 mm/min and groove width of 1.2 mm gives maximum tensile strength of 344.79 MPa, hardness value of 283 and wear of 1.290 mm 3 . The microstructure and mechanical properties such as tensile strength, hardness and wear has been enhanced by addition of niobium in the Al7075 metal. The optimum process parameter from signal-to-noise ratio is used to identify the maximum tensile strength, hardness and wear behaviour. The optimized values are rotational speed of 700 rpm, transverse speed of 40 mm/ min and groove width of 0.6 mm are obtained from signal-to-noise ratio.